082 The gastrointestinal microbiome in parkinson's disease: impacts of motor and non-motor features, medications, lifestyle and diet. (29th July 2019) - Lubomski, Michal; Tan, Ai Huey; Lim, Shen-Yang; Holmes, Andrew; Davis, Ryan L; Sue, Carolyn M
Abstract : Introduction: The human gastrointestinal microbiome (GM) has been proposed to be integral in the pathogenesis of Parkinson's disease (PD). Evidence supports a bidirectional interaction between the brain and the gut that is mediated by the GM. Dysbiosis of the GM is believed to negatively influence vital physiological functions in many diseases. Methods: We reviewed the literature on changes in human physiological function associated with gut microbial community states in PD. In particular, we evaluated the literature for effects of GM dysbiosis on motor and non-motor features, dietary and lifestyle factors and medication use in PD. Results: Altered GM profiles in PD have been suggested to disrupt vital signalling pathways within the microbiota-gut-brain axis, integral to regulating physiological digestive function and metabolic homeostasis. Unfavourable variations in the GM have been shown to perturb mood (anxiety/depression), cognition, perception (hallucinations/delusions), gastrointestinal motility, including constipation in PD. Further, varied clinical motor phenotypes, including postural instability and gait disturbance have been attributed to alterations in the GM, in addition to the use of catechol-O-methyltransferase inhibitors, anticholinergics and levodopa. Variations in dietary and lifestyle factors have also been inferred to cause alterations in GM profiles, including caffeine consumption, macronutrient intake, smoking and the effects of ageing and exercise. Conclusions: It is apparent from the mounting evidence that alterations in the GM are intimately involved in PD pathogenesis. However, the GM can also be modulated by dietary, lifestyle and treatment factors that may influence motor and non-motor features as well as disease progression.